Handbook of studies on men & masculinities - Kimmel, Michael S.; Hearn, Jeff; Connell, R. W. (SAGE, 2005)
The Handbook of Studies on Men and Masculinities is an interdisciplinary and international culmination of the growth of men′s studies that also offers insight about future directions for the field. The Handbook provides a broad view of masculinities across the social sciences, with the inclusion of important debates in some areas of the humanities and natural sciences. Editors Michael S Kimmel, Jeff Hearn, and Robert W Connell have assembled an esteemed group of contributors who are among the best-known experts in their particular fields. The Handbook of Studies on Men and Masculinities provides scholars, researchers, and students with the most current, incisive scholarship available for the men′s studies area of gender studies. It is a vital resource for those interested in the practical or cultural issues about men, boys and gender, as well as an excellent addition to any academic library.